Functional multilayered polymeric nanocarriers for delivery of mitochondrial targeted anticancer drug curcumin. (10th February 2016) - Grancharov, Georgy; Gancheva, Valeria; Kyulavska, Marya; Momekova, Denica; Momekov, Georgi; Petrov, Petar
Abstract: We report on the preparation of novel functional multilayered polymeric nanocarriers for targeted cell delivery from a binary mixture of amphiphilic poly(ethylene oxide)-poly(ε-caprolactone)-b-poly(ethylene oxide) (PEO113 -b-PCL70 -b-PEO113 ) and poly(2-(dimethylamino)ethyl methacrylate)-b-poly(ε-caprolactone)-b-poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA20 (TPP+) -b-PCL70 -b-PDMAEMA20 (TPP+) ) triblock copolymers. PEO113 -b-PCL70 -b-PEO113 was synthesized by copper mediated "click" coupling reaction of preliminary modified commercially available PEO monomethyl ether and PCL-diol. By design, the two outer PEO blocks were linked to the middle PCL block via cleavable acetal groups that allow release of PEO from the carrier in acidic conditions. PDMAEMA20 -b-PCL70 -b-PDMAEMA20 was obtained by ATRP of DMAEMA initiated by a bi-functional PCL macroinitiator. Then, PDMAEMA blocks were decorated with mitochondria targeting triphenylphosphonium (TPP + ) ligands (12.5 mol% to DMAEMA units). Dynamic light scattering (DLS) and transmission electron microscopy (TEM) analysis confirmed formation of uniform nano-sized spherical micelles in aqueous media. Based on copolymer architecture, composition and properties in water, a three-layered structure comprising a hydrophobic PCL core, a PEO/PDMAEMA (TPP+) middle layer, and a PEO outer layer is suggested. The cytotoxicity of polymer nanocarriers with and without the anticancer drug curcumin and their cell internalization were assessed as well. Preliminary results revealed the ability of the developed polymeric nanocarriers to deliver the cargo into the cells, which makes them promising candidates for targeted cell delivery. Graphical abstract: Highlights: Novel functional nanocarriers for targeted cell delivery are developed. The nanocarriers are based on amphiphilic block copolymer blend. Curcumin loaded nanocarriers possess efficient toxicological profile. They can be readily internalized into cells and deliver curcumin.